Meningkatkan kompetensi profesional guru melalui pendampingan penulisan karya tulis ilmiah di SMPN 3 Bissappu Bantaeng - Syamsidah Syamsidah; Ratnawati T; Amir Muhiddin (Seminar Nasional Pengabdian Kepada Masyarakat, 2020)
The Community Service Activities aims to improve the professional competency skills of teachers related to writingscientific papers, especially how to make classroom action research. This is important because each teacher can provide data andinformation related to the learning models and methods that they have been provided to their students, the results of models andmethods used and how to get the best solution. Classroom action research can not only be used as a reflection of learningactivities in the classroom but also can provide new empirical facts that can be used as a comparison as well as choosing the bestlearning methods and models. This activity was conducted at 3 SMP Negeri 3 Bissappu, Bantaeng Regency with a total of 15teachers. The training method included lectures, discussions, and practice. The topics of lecture and discussion were: 1) How toprepare proposals including how to choose the problem, objectives, benefits, theoretical studies and class action research cycles,2) The relationship between the formulation of the problem with the study of theories, frameworks, and hypotheses of action, 3)Data collection techniques and data analysis techniques, 4) The practice of making proposals as well as the percentage ofproposal results. After evaluating the training and mentoring process, the results show that: 1) Participants were serious andactively participating in the training, 2) More than 80% of participants already understood and knew how to prepare a goodproposal and they were able to practice and present their proposal.